Early Designs for the Occlusal Anatomy of Posterior Denture Teeth: Part III - Robert L. Engelmeier, DMD, MS (Journal of Prosthodontics, 2005)
Part III of this series of articles, like Part II, reviews the pioneering efforts in the 19th century to improve the quality of artificial teeth.